PROBLEMATIKA DALAM TAKE OVER DEBITUR DALAM PERJANJIAN KREDIT KEPEMILIKAN RUMAH DI BANK TABUNGAN NEGARA CABANG SAMARINDA - harly harly (Universitas 17 Agustus 1945 Samarinda, 2013)
ABSTRACTAn implementation over the debtor generally occurs because the creditors in this case the BTN did not want to suffer, so as to avoid the auction items made bail Mail Transfer the Debtor. So according to the author's opinion that should the BTN in screening prospective customer must go through careful credit analysis, it is related to the temperament (character), ability (capacity), equity (capital), collateral (collateral) and economic conditions (condition of economy ) of the prospective customer, so hopefully does not happen in the future installment arrears. Or in other words that the transition is not accompanied by the customer with no resolution.In a letter made over the debtor between the BTN with the home buyer who gets mortgage facility of BTN, all rights and obligations of the debtor will switch to the home buyers. Besides, with the manufacture of letters over the debtor, then the position of the home buyers will turn out to be the debtor of the BTN, and also means that there is a legal relationship between the parties to the original debtor BTN happened when the treaty transfer credit debt was considered to remove or have ends.If in the future the debtor in default, it can be executed against the object of mortgage insurance (Law no. 4 of 1996), the agreement between recipient of mortgage lenders (Law no. 4 of 1996) and the giver of mortgage borrowers (Law no. 4 in 1996). So that the proceeds from the sale of mortgage collateral objects (Law no. 4 of 1996) could be beneficial to both parties.